Altas habilidades/superdotação na rede pública municipal de Cascavel: uma análise na perspectiva da psicologia histórico-cultural - Alves, Veronice Suriano (2017)
This research aims at deepening the knowledge about high skills and giftedness (AH / SD), from the perspective of historical-cultural psychology, providing subsidies that contribute to the effectiveness of the AH / SD public policies, unfolding in the following secondary objectives: the pedagogical coordinators and teachers of the Municipal Network of Cascavel conceptualize and characterize AH / SD; To verify the contribution of historical-cultural psychology to the understanding of the teaching and learning processes of students with AH / SD; To investigate the referrals by the Municipal Department of Education in the face of the challenge of preparing teachers for the care of students with AH / SD. Initially, we investigated the state of knowledge in the Database of the Digital Library of Theses and Dissertations (BDTD), between 2005 and 2015, with the descriptors: high skills / giftedness, historical-cultural psychology and public policies. Of this refinement, 25 researches were found, of which only one turned to the historical-cultural theory and one to the Foucaultian theory, being based on non-critical theories. Also, it was sought to verify how the municipal education network treats the continued formation in this subject, as well as the concept and characteristics of AH / SD presented by these professionals. For this study, a field survey was carried out, applying a questionnaire to the Pedagogical Coordinators of the 62 municipal schools of Cascavel. Among these coordinators, 25 indicated, in the school where they worked, students with AH / SD indicators, in the year 2015. With the possession of such information, in 2016, the research continued in these schools, involving 31 teachers’ regents of the early years. The collected data were analyzed based on the Content Analysis (BARDIN, 1977). It was found that 52% of pedagogical coordinators and 52% of teachers understand that students with AH / SD, stand out in all areas of knowledge; 8% of the coordinators and 16% of the teachers understand that these students present AH / SD in several areas; 12% of coordinators and 22% of teachers understand that students have AH / SD in one area, while 28% of coordinators and 13% of teachers point out that AH / SD are present in one or several areas of knowledge. For Vygotsky, subjects with AH / SAD do not present a general ability, since they are culturally constituted, through their activities, within the complex movement established dialectically in their social relations. Regarding the characteristics, the research reveals that 71% of the teachers indicate that the students with AH / SD present academic abilities; 26% point to creativity; 61% emphasize emotional skills and 58% emphasize intellectual ability, and the leadership and motor skills indicated in current official documents are disregarded. It is concluded that the conceptual fragilities found are related to the teacher training process and, thus, the need for public policies that contemplate initial and continued specific training on AH / SD emerges. In this way, the relevance of the contribution of historical-cultural psychology to the development of the human psyche is emphasized, and further research is needed to address this theme